Crowdfunding's potential in the South African entrepreneurial ecosystem: Is there a role to play in catalysing venture capital? - Bennot, Adam (Research of GSB, 2018)
The purpose of this research is to examine the potential influence crowdfunding could have on the early-stage financing ecosystem in South Africa. Particularly, how it could affect entrepreneurial deal flow as well as inform the venture capital decision-making process. The primary aim of this research is to explore the due diligence practices and perceptions of venture capital fund managers, angel investors and entrepreneurs to ascertain the extent to which crowdfunding can be incorporated into the South African entrepreneurial ecosystem and inform the investment process. The researcher, therefore, intends that this research enhance venture capital investment decision-making capabilities while adding to the existing body of knowledge on early-stage investing. Ultimately, it is hoped that the results of this in-depth study will accelerate the development of the venture capital industry in South Africa and unlock early-stage seed capital whilst promoting entrepreneurial activity and possibly providing insight and guidance to entrepreneurs faced with the challenging task of accessing financing. The researcher anticipates that the finding of this research will likely be of interest to players in the VC and early-stage new venture financing industry, including fund managers, investors, entrepreneurs and crowdfunding providers. The findings might impact the investment process, which has direct implications for capital providers, fund managers and fund seekers. Furthermore, this research might be of interest to researchers and those in academia concerned with this field, who might then conduct similar studies or decide to expand the research in new directions. By investigating crowdfunding's potential within the VC investment decision-making process, it is anticipated that the findings might be fed back into the marketplace and inform future VC investments in South Africa.